Hedging in Newspaper Headlines Written by Indonesian and American Writers - Sa`adah, Ma`rifatus; Hardjanto, Tofan Dwi (Lexicon, 2023)
Newspaper headlines contain the main and most important news articles in the newspaper. They are aimed to present news as accurately as possible. On the other hand, newspapers are also a company that aims to make profit from every news that is published. Thus, they have other interests besides conveying news as accurately as possible. One possible strategy to balance these two different interests is to use a hedging strategy. This research is an attempt to find out the forms and functions of hedging expressions used in headlines from two newspapers, The Jakarta Post and New York Times newspaper. The headlines that are used as the object of study are limited to the headlines containing news about the pandemic covid-19. This study also compares the forms and frequency of hedging expressions used in The Jakarta Post and New York Times. The data were quantitatively analyzed with a help of concordance software Wordsmith 4.0 (Scott, 2004). A qualitative analysis method was also conducted to classify the forms and functions of hedging expressions. A taxonomy proposed by Salager-Meyer (1997) was employed to analyze the forms of hedging expressions and Hyland (1996b) taxonomy was applied to identify the functions of hedging expressions serve in newspaper headlines. The results show that both groups of writers tend to employ hedging expressions in terms of the forms and functions in the similar way. Moreover, there was no significant difference in the use of hedging expressions by two groups of writers.